Respuesta :
Use the rules of logarithm:
1. log(x)+log(y)=log(xy)
log(x)-log(y)=log(x/y)
2. k*log(x) = log(x^k)
log(x)/k = log(x^(1/k))
log(2z)+2log(2x)+4log(9y)+12log(9x)−2log(2y)
=log(2z)+log(4x^2)+log(9^4y^4)+log(9^12x^12)−log(4y^2)
=log(2z)+log(4x^2)+log(6561y^4)+log(282429536481x^12)−log(4y^2)
=log(59296646043258912 * x^14 * y^6 * z)
1. log(x)+log(y)=log(xy)
log(x)-log(y)=log(x/y)
2. k*log(x) = log(x^k)
log(x)/k = log(x^(1/k))
log(2z)+2log(2x)+4log(9y)+12log(9x)−2log(2y)
=log(2z)+log(4x^2)+log(9^4y^4)+log(9^12x^12)−log(4y^2)
=log(2z)+log(4x^2)+log(6561y^4)+log(282429536481x^12)−log(4y^2)
=log(59296646043258912 * x^14 * y^6 * z)
The equivalent expression of the logarithmic expression is log(2 *9¹⁶x¹⁴y²z)
How to rewrite the expression?
The logarithmic expression is given as;
log(2z) + 2log(2x) + 4log(9y) + 12log(9x) − 2log(2y)
Express as exponents
log(2z) + log(2x)² + log(9y)⁴ + log(9x)¹² − log(2y)²
Apply the product rule of logarithm
log(2z * (2x)² * (9y)⁴ * (9x)¹²) − log(2y)²
Evaluate
log(2z * 4x² * 9⁴y⁴ * 9¹²x¹²) − log(2y)²
Apply the quotient rule of logarithm
log(2z * 4x² * 9⁴y⁴ * 9¹²x¹²/(2y)²)
Evaluate
log(2z *x² * 9⁴y² * 9¹²x¹²)
This gives
log(2 *9¹⁶x¹⁴y²z)
Hence, the equivalent expression is log(2 *9¹⁶x¹⁴y²z)
Read more about logarithmic expressions at:
https://brainly.com/question/25710806
#SPJ2